Study of the Oriental genus Alishania Vilbaste (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of one new species - Lu, Lin; Zhang, Yalin (Zootaxa, 2016)
The Oriental leafhopper genus Alishania Vilbaste, is reviewed and includes A. formosana, A. fodingensis, A. attenuata and a new species, A. quadrilamina sp. nov., found during a survey of leafhoppers in Xizang and described here. A key to males of Alishania species, together with descriptions, a checklist and figures are provided. Based on the structure of the aedeagus, Alishania is here transferred from subtribe Opsiina to subtribe Circuliferina of tribe Opsiini.